The Impact of News Photos on Support for Military Action. (1st October 2016) - Soroka, Stuart; Loewen, Peter; Fournier, Patrick; Rubenson, Daniel
Abstract : Drawing on two experiments embedded in online surveys, this article examines the impact of news photos on support for military action. In 2011, respondents were asked about support for ongoing military involvement in Afghanistan while being randomly exposed to one of two photos—one of a soldier with a child, the other of a soldier with a gun. The former photo increased expressed support for war; and the effect was greater for those who self-identify as being very interested in international affairs. Three years later, a follow-up experiment was fielded that looked both at the past intervention in Afghanistan and ongoing interventions in Syria; results were very similar. Both experiments speak to the potentially profound role of mass media in generating support (or not) for foreign military engagements, and the increased impact of frames on those who are more attentive to the issue domain.